Integrative Network Pharmacology and Molecular Dynamics Simulation Uncover Key Molecular Targets of Curcumin and Its Derivatives in Colorectal Cancer - Usama Ilahi; Muhammad Suleman; Abrar Mohammad Sayaf; Muhammad Rizwan; Fazal Akbar; Zafar Ali; Haji Khan; Zahid Hussain; Mohammad Ali; Hadi M. Yassine; Abdullah A. Shaito; Sergio Crovella (Journal of Pharmaceutical Innovation, 2026)

Toward a Vaccine Against Multidrug-Resistant Elizabethkingia anophelis: Comprehensive Immunoinformatics-Based Design of a Multi-Epitope Vaccine and mRNA Construct - Muhammad Hanzala; Rana Zohaib Abbas; Mahnoor Habib; Allah Rakha Yaseen; Muhammad Suleman; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Sehrish Firyal (Probiotics and Antimicrobial Proteins, 2026)

Functional and structural characterization of the SARS-CoV-2 spike N481K mutation - Maria K. Smatti; Hebah Al-Khatib; Muhammad Suleman; Muna Nizar; Hala Abo Khalid; Ruaa Ismail; Gheyath K. Nasrallah; Hadi M. Yassine (Archives of Virology, 2026)
Background: Selective pressure drives SARS-CoV-2 evolution, with spike RBD substitutions shaping ACE2 binding and antibody escape. N481K RBD mutation emerged early in Qatar (2020) and later re-emerged globally, reaching near-fixation by 2024–2025, yet its functional significance remained unexplored. Methods: We analyzed the temporal and geographic circulation of N481K across > 17 million SARS-CoV-2 genomes (2020–2025). Structural effects were assessed using modeling, docking, and molecular dynamics. Functional impact was evaluated using VSV pseudovirus neutralization tests with sera from infected individuals (n = 48) and vaccinated cohorts: mRNA (n = 16), Sinopharm (n = 45), and AstraZeneca (n = 28). Results: N481K was detected in 4.14% (703,777/17,016,111) of global genomes and reached near-fixation (> 90%) in dominant Omicron lineages by 2024, with prevalence rising from 71.5% in early 2024 to 94.4% by week 36 of 2025. Structural analyses showed a 0.706 Å RMSD deviation and higher ACE2 docking affinity (–313 vs. − 308 kcal/mol) compared to the wild-type (WT) RBD. Molecular dynamics confirmed increased stability and lower binding free energy for N481K versus WT (–77.07 ± 0.90 vs. − 43.09 ± 0.98 kcal/mol). Among samples with detectable WT neutralization (n = 89), mean neutralization declined from 69.76% (WT) to 42.47% (N481K) (p

The Influence of Policy Indicators on Circular Economy Metrics in Australia: Application of Asymmetric Analysis - Suleman Sarwar; Afifa Qadeer; Rida Waheed; Ghazala Aziz; Muhammad Wasim Hussan (Circular Economy and Sustainability, 2026)

From Sequence to Solution: Computational Design of a Multi-Epitope Vaccine Candidate Against Francisella tularensis - Muhammad Suleman; Allah Rakha Yaseen; Ayman Naeem; Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Misbah Khan (Probiotics and Antimicrobial Proteins, 2026)

Chemical contaminants and fish: implications for health and ecosystem sustainability - Muhammad Sohail; Mohammad Ali Nematollahi; Sardar Suleman; Syed Sikandar Habib (Environmental Monitoring and Assessment, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Targeting the VP24-Karyopherin-α Interface With Phytocompounds: A Structure-Based Molecular Screening and Dynamic Simulation Approach to Rescue Immune Responses Against Ebola Virus - Mohammed A. Alshehri; Mohammed Alissa; Muhammad Suleman (Journal of Pharmaceutical Innovation, 2026)

Targeting 3Cpro of Enterovirus D68 with Medicinal Phytocompounds Using Structure-Based Molecular Screening and Molecular Simulation Approaches to Rescue the Host Immune Response - Muhammad Suleman; Abrar Mohammad Sayaf; Fazal Akbar; Mohammed Alissa; Ghadah S. Abusalim; Ghada M. Alnafesah; Kar Kheng Yeoh; Sergio Crovella; Hadi M. Yassine (Journal of Pharmaceutical Innovation, 2026)

Genetically Encoded Near-Infrared Fluorescent Proteins for Viral Imaging and Detection: A Mini-Review - Fakhrul Hassan; Abbas Khan; Muhammad Suleman; Faez Iqbal Khan; Ijaz Gul (Current Microbiology, 2026)

Development of a Novel Pan-Species Multi-Epitope Vaccine (PS-MEV) Targeting Nine Staphylococcus Species to Combat Antibiotic Resistance - Allah Rakha Yaseen; Muhammad Suleman; Mahnoor Habib; Tehreem Arshad; Muskan Fatima; Ayesha Arif; Hafiza Sadia Rasool (Probiotics and Antimicrobial Proteins, 2026)

Immunoinformatic based designing of highly immunogenic multi-epitope subunit vaccines to stimulate an adaptive immune response against Junin virus - Mohammed Alissa; Abdullah Alghamdi; Suad A. Alghamdi; Muhammad Suleman (Molecular Diversity, 2025)

Leveraging immunoinformatic for the rational design of highly immunogenic multi-epitope subunit vaccines against Dugbe virus: a molecular docking and simulation approach - Ali khan; Safir Ullah Khan; Fazal Akbar; Fakhrul Hassan; Zafar Ali; Haji Khan; Shahid Ali; Muhammad Yousaf; Hadi M. Yassine; Sergio Crovella; Muhammad Suleman (In Silico Pharmacology, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Monochalcogenide-based retina-inspired photosynapses for energy-efficient neuromorphic computing and artificial visual system application - Muhammad Riaz; Zeesham Abbas; Jiayi Li; Syed Khizar Abbas Abidi; Muhammad Hussain; Syed Hassan Abbas Jaffery; Muhammad Suleman; Haider Abbas; Diing Shenp Ang; Sajjad Hussain; Jongwan Jung (Chemical Engineering Journal, 2025)

Structure-Based Molecular Screening and Simulation Approaches To Inhibit Marburg Virus VP35 Protein Using Medicinal Phytocompounds for Restoring Host Immune Response - Mohammed A. Alshehri; Mohammed Alissa; Muhammad Suleman (Journal of Pharmaceutical Innovation, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Effects of bacteriophage supplementation on performance, gut health and blood biochemistry in broilers challenged with necrotic enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Saima; Muhammad Suleman; Mian Muhammad Awais; Sohail Ahmad (Research in Veterinary Science, 2025)

DusVax: a universal pan-viral multi-epitope vaccine (PV-MEV) for pandemic preparedness against ten high-priority viral pathogens - Allah Rakha Yaseen; Muhammad Suleman; Mahrukh Afzal; Hania Usama; Warda Ashfaq; Sehrish Firyal; Ayesha Arif; Amna Latif; Ali Asghar; Abdul Salam Qadri (The Nucleus, 2025)

Curcumin induces apoptosis via downregulation of SKP2 and induction of GADD45A/CDKN1A expression through generation of ROS in cutaneous T-cell lymphoma cells - Shilpa Kuttikrishnan; Muhammad Suleman; Fareed Ahmad; Zahwa Mariyam; Ummu Habeeba; Kirti S. Prabhu; Joerg Buddenkotte; Martin Steinhoff; Shahab Uddin (Toxicology and Applied Pharmacology, 2025)

Mapping mangroves land suitability using machine learning and MCDM in the Indus Delta, Pakistan - Sher Shah Hassan; Muhammad Ajmal; Muhammad Arif Goheer; Zainab Ali; Muhammad Suleman (Theoretical and Applied Climatology, 2025)

A Novel Transfer Learning-Based OFDM Receiver Design for Enhanced Underwater Acoustic Communication - Muhammad Adil; Songzuo Liu; Suleman Mazhar; Ayman Alharbi; Honglu Yan; Muhammad Muzzammil (Journal of Marine Science and Engineering, 2025)
The underwater acoustic (UWA) communication system faces challenges due to environmental factors, extensive multipath spread, and rapidly changing propagation conditions. Deep learning based solutions, especially for orthogonal frequency division multiplexing (OFDM) receivers, have been shown to improve performance. However, the UWA channel characteristics are highly dynamic and depend on the specific underwater conditions. Therefore, these models suffer from model mismatch when deployed in environments different from those used for training, leading to performance degradation and requiring costly, time-consuming retraining. To address these issues, we propose a transfer learning (TL)-based pre-trained model for OFDM based UWA communication. Rather than training separate models for each underwater channel, we aggregate received signals from five distinct WATERMARK channels, across varying signal to noise ratios (SNRs), into a unified dataset. This diverse training set enables the model to generalize across various underwater conditions, ensuring robust performance without extensive retraining. We evaluate the pre-trained model using real-world data from Qingdao Lake in Hangzhou, China, which serves as the target environment. Our experiments show that the model adapts well to these challenging environment, overcoming model mismatch and minimizing computational costs. The proposed TL-based OFDM receiver outperforms traditional methods in terms of bit error rate (BER) and other evaluation metrics. It demonstrates strong adaptability to varying channel conditions. This includes scenarios where training and testing occur on the same channel, under channel mismatch, and with or without fine-tuning on target data. At 10 dB SNR, it achieves an approximately 80% improvement in BER compared to other methods.

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Unlocking the Therapeutic Potential of Alisertib in Breast Cancer: An In-Depth Exploration of Molecular Targets Using Network Pharmacology and Gene Expression Network - Suad A. Alghamdi; Mohammed Alissa; Muhammad Suleman (Journal of Pharmaceutical Innovation, 2025)

Effects of replacing antibiotics with probiotics and antimicrobial peptides on performance, gut health, carcass traits, meat quality, and welfare in broilers infected with Eimeria and Clostridium perfringens - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Suleman; Muhammad Shabir Shaheen; Muhammad Shahbaz Zafar; Sohail Ahmad (Tropical Animal Health and Production, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Pyocins and Beyond: Exploring the World of Bacteriocins in Pseudomonas aeruginosa - Muhammad Suleman; Allah Rakha Yaseen; Shahbaz Ahmed; Zoha Khan; Asma Irshad; Afsah Pervaiz; Hafiza Hiba Rahman; Muteeba Azhar (Probiotics and Antimicrobial Proteins, 2025)

The Baroch Nala section (NE Pakistan): A new PETM standard for the eastern Tethys - Mubashir Ali; Giovanni Coletti; Eduardo Garzanti; Thierry Adatte; Sébastien Castelltort; Pietro Sternai; Andrea Benedetti; Elisa Malinverno; Luca Mariani; Jorge E. Spangenberg; Suleman Khan; Daniela Basso; et al. (Marine and Petroleum Geology, 2025)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Correction: A detailed investigation of Jutana formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

A detailed investigation of Jutana Formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

Enhancing the Quality and Fruit Yield of Sweet Cherry (Prunus Avium) Cultivars by Foliar Application of Boron - Muhammad Sajid; Abdul Basit; Syed Tanveer Shah; Ayesha Khan; Izhar Ullah; Muhammad Bilal; Muhammad Suleman Khan; Waleed Khan (Applied Fruit Science, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Role of nuclear energy, geothermal energy, agriculture, and urbanization in environmental stewardship - Muhammad Ramzan; Ummara Razi; Muhammad Usman; Suleman Sarwar; Amogh Talan; Hardeep Singh Mundi (Gondwana Research, 2024)

Surveillance of pesticide residues in tomato and eggplant and assessment of acute and chronic health risks to the consumers in Pakistan - Aasma Bibi; Farida Anjum; Syed Roohul Hussain; Abdul Ahad; Azeem Ud Deen; Muhammad Suleman; Bilal Jan (Environmental Science and Pollution Research, 2023)

Combined Coagulation-Electrocoagulation Treatment of Urban, Peri-urban, and Textile Wastewaters: Process Evaluation and Sludge Setting Characteristics - Suleman Arshad; Waqar Ali Khan; Muhammad Tahir Ishfaq; Muhammad Usman (Water Conservation Science and Engineering, 2023)

Emerging trends of green hydrogen and sustainable environment in the case of Australia - Afifa Qadeer; Muhammad Wasim Hussan; Ghazala Aziz; Rida Waheed; Suleman Sarwar (Environmental Science and Pollution Research, 2023)

Development of conserved multi-epitopes based hybrid vaccine against SARS-CoV-2 variants: an immunoinformatic approach - Allah Rakha Yaseen; Muhammad Suleman; Abdul Salam Qadri; Ali Asghar; Iram Arshad; Daulat Munaza Khan (In Silico Pharmacology, 2023)

The influence of civilized city honorary title on the urban innovation capacity - Jiabin han; Ziyi Chen; Muhammad Zeeshan; Alam Rehman; Irfan Ullah; Suleman Sarwar (Environment, Development and Sustainability, 2023)

Repositioning of experimentally validated anti-breast cancer peptides to target FAK-PAX complex to halt the breast cancer progression: a biomolecular simulation approach - Abbas Khan; Shengzhou Shan; Tayyba Fatima Toor; Muhammad Suleman; Yanjing Wang; Jia Zhou; Dong-Qing Wei (Molecular Diversity, 2023)

Correction to: Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2023)

Personal protective equipment (PPE) disposal during COVID-19: An emerging source of microplastic and microfiber pollution in the environment - Muhammad Tariq Khan; Izaz Ali Shah; Md Faysal Hossain; Nasrin Akther; Yanbo Zhou; Muhammad Sajawal Khan; Muayad Al-shaeli; Muhammad Suleman Bacha; Ihsanullah Ihsanullah (Science of The Total Environment, 2023)

Dynamic linkages between Islamic equity indices, oil prices, gold prices, and news-based uncertainty: New insights from partial and multiple wavelet coherence - Muhammad Asif Khan; Farhad Khan; Arshian Sharif; Muhammad Tahir Suleman (Resources Policy, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Empirical relationship between creativity and carbon intensity: a case of OPEC countries - Ghazala Aziz; Suleman Sarwar; Muhammad Shahbaz; Muhammad Nasir Malik; Rida Waheed (Environmental Science and Pollution Research, 2022)

Thermal Plasticity and Cotton Production Enhancing Attributes of Phosphate-Solubilizing Bacteria from Cotton Rhizosphere - Suleman Haider Shah; Muhammad Baqir Hussain; Zahir Ahmad Zahir; Tanveer Ul Haq; Amar Matloob (Journal of Soil Science and Plant Nutrition, 2022)

Morphology of testis, sperm, and spermatheca in two capable hybridized termite species indicates no interspecific reproductive isolation - Zahid Khan; Mian Sayed Khan; Suleman; Nehaz Muhammad; Haroon; Xiao-Hong Su; Lian-Xi Xing (International Journal of Tropical Insect Science, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Late Cretaceous pelagic laminites at the northwestern margin of Indian plate, Pakistan: implications for basin bathymetry and ophiolite emplacement - Sajjad Ahmad; Suleman Khan; Bilal Wadood; Asad Naseer; Muhammad Noman; Jamal Wadood; Muhammad Muslim (Carbonates and Evaporites, 2021)

The sedimentological and stratigraphical analysis of the Paleocene to Early Eocene Dungan Formation, Kirthar Fold and Thrust Belt, Pakistan: implications for reservoir potential - Sajjad Ahmad; Bilal Wadood; Suleman Khan; Abd Ullah; Ghazi Mustafa; Muhammad Hanif; Hasbee Ullah (Journal of Sedimentary Environments, 2020)

Molecular and morphological discrimination of Chrysanthemum indicum using allele-specific PCR and T-shaped trichome - Suleman Abid; Lalitha Kaliraj; Muhammad Huzaifa Arif; Joon Hurh; Jong Chan Ahn; Deok Chun Yang; Seok-Kyu Jung (Molecular Biology Reports, 2020)

Morphological and genetic characterisation of Centrorhynchus clitorideus (Meyer, 1931) (Acanthocephala: Centrorhynchidae) from the little owl Athene noctua (Scopoli) (Strigiformes: Strigidae) in Pakistan - Qing Zhao; Nehaz Muhammad; Hui-Xia Chen; Jun Ma; Suleman; Liang Li (Systematic Parasitology, 2020)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

The impact of carbon emission and forest activities on health outcomes: empirical evidence from China - Muhammad Umar Farooq; Umer Shahzad; Suleman Sarwar; Li ZaiJun (Environmental Science and Pollution Research, 2019)

CO2 foam for enhanced oil recovery (EOR) applications using low adsorption surfactant structure - Muhammad Sagir; Muhammad Mushtaq; Muhammad Bilal Tahir; Muhammad Suleman Tahir; Sami Ullah; Khurum Shahzad; Umer Rashid (Arabian Journal of Geosciences, 2018)

Ridge sowing of sunflower (Helianthus annuus L.) in a minimum till system improves the productivity, oil quality, and profitability on a sandy loam soil under an arid climate - Ahmad Sher; Muhammad Suleman; Abdul Qayyum; Abdul Sattar; Allah Wasaya; Muhammad Ijaz; Ahmad Nawaz (Environmental Science and Pollution Research, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

EDTA-enhanced phytoremediation of contaminated calcareous soils: heavy metal bioavailability, extractability, and uptake by maize and sesbania - Vishandas Suthar; Kazi Suleman Memon; Muhammad Mahmood-ul-Hassan (Environmental Monitoring and Assessment, 2014)